House in the General System of Financial Relations Farm Finance - Mamayusupova Shakhina Ulugbek kizi (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Financial decisions of households in a certain period set (specify) their financial behavior will give. Subjective motives in making financial decisions, due to the large role of priorities and constraints such behavior is very diverse. On top of that, the house financial behavior of farms is dynamic, fast is a variable process. In this regard, the house quantitative and qualitative financial decisions of farms positions (including marketing), economy, research from the perspectives of sociology and social psychology will be done. This is savings and investment of the household is happening. These are investment risk reduction and financial assets households in order to increase the stability of their portfolio real based on diversification of asset portfolio manifested in the formation of the accumulation strategy is happening.